Utility of the SERPINC1 Gene Test in Ischemic Stroke Patients With Antithrombin Deficiency - Kim, Seondeuk; Lee, Woo-Jin; Moon, Jangsup; Jung, Keun-Hwa (Frontiers in Neurology, 2022)
Objective: Antithrombin (AT) plays a critical role in the coagulation system, and its deficiency induces hypercoagulability. AT deficiency is caused not only by inherited variants in the SERPINC1 gene but also by acquired conditions. Therefore, AT deficiency alone could not ensure the presence of the SERPINC1 mutation. We evaluated the utility of the SERPINC1 gene test in ischemic stroke, an important clinical type of arterial thrombosis. Methods: This retrospective, observational study investigated symptomatic patients who underwent the SERPINC1 gene test because of decreased AT activity (<80%) during 2009-2021 at a tertiary hospital. For the detection of sequence variants in the SERPINC1 gene, direct Sanger sequencing and multiplex ligation-dependent probe amplification were performed. The phenotypes of patients with SERPINC1 gene mutations were examined, and the conditions associated with the pathogenic variants were analyzed. Results: In our cohort (n=19), 13 of 19 patients (68.4%) had the pathogenic variant of the SERPINC1 gene. Ischemic stroke (n=7) was significantly associated with the pathogenic variants (p= 0.044), and the pathogenicity detection rate was 100%. For any kind of arterial thrombosis (n=8), the detection rate of the pathogenic variant was 87.5%, but was not statistically significant (p=0.177). The detection rates of the pathogenic variant in ischemic stroke or arterial thrombosis groups were both higher than those in the venous thrombosis-only group (54.5%). Conclusion: The SERPINC1 gene test was useful in determining the cause of AT deficiency-related arterial thrombosis, especially ischemic stroke. We propose the diagnostic flow of SERPINC1-related ischemic stroke.